Aging and Strength Training Influence Knee Extensor Intermuscular Coherence During Low- and High-Force Isometric Contractions - Walker, Simon; Avela, Janne; Wikgren, Jan; Meeusen, Romain; Piitulainen, Harri; Baker, Stuart N.; Parviainen, Tiina M. (Frontiers in Physiology, 2019)
Aging is associated with reduced maximum force production and force steadiness during low-force tasks, but both can be improved by training. Intermuscular coherence measures coupling between two peripheral surface electromyography (EMG) signals in the frequency domain. It is thought to represent the presence of common input to alpha-motoneurons, but the functional meaning of intermuscular coherence, particularly regarding aging and training, remain unclear. This study investigated knee extensor intermuscular coherence in previously sedentary young (18‒30 years) and older (67‒73 years) subjects before and after a 14-week strength training intervention. YOUNG and OLDER groups performed maximum unilateral isometric knee extensions (100% MVC), as well as force steadiness tests at 20% and 70% MVC, pre- and post-training. Intermuscular (i.e. EMG-EMG) coherence analyses were performed for all (three) contraction intensities in vastus lateralis and medialis muscles. Pre-training coefficient of force variation (i.e. force steadiness) and MVC (i.e. maximum torque) were similar between groups. Both groups improved MVC through training, but YOUNG improved more than OLDER (42 ± 27Nm versus 18 ± 16Nm, P = 0.022). Force steadiness did not change during 20% MVC trials in either group, but YOUNG demonstrated increased coefficient of force variation during 70% MVC trials (1.28 ± 0.46 to 1.57 ± 0.70, P = 0.01). YOUNG demonstrated greater pre-training coherence during 20% and 70% MVC trials, particularly within the 8‒14 Hz (e.g. 20%: 0.105 ± 0.119 versus 0.016 ± 0.009, P = 0.001) and 16‒30 Hz (20%: 0.063 ± 0.078 versus 0.012 ± 0.007, P = 0.002) bands, but not during 100% MVC trials. Strength training led to increases in intermuscular coherence within the 40‒60 Hz band during 70% MVC trials in YOUNG only, while OLDER decreased within the 8‒14 Hz band during 100% MVC trials. Age-related differences in intermuscular coherence were observed between young and older individuals, even when neuromuscular performance levels were similar. The functional significance of intermuscular coherence remains unclear, since coherence within different frequency bands did not explain any of the variance in the regression models for maximum strength or force steadiness during 20% and 70% MVC trials.